Climate Resilience Politics: Flood Disaster Governance and Socio-Economic Vulnerability Among Urban Traders in Palangka Raya - Wening Mustikaningsih; Annisa Rizki Ananda (Politeia : Journal of Public Administration and Political Science and International Relations, 2026)
This research explores how recurrent river flooding and extreme rainfall reshape the socio-economic vulnerability—specifically exposure, sensitivity, and adaptive capacity—of traditional traders in Pelabuhan Rambang, Palangka Raya. A qualitative case study design was employed, and data from nine key informants were analyzed using a hybrid deductive–inductive coding approach via NVivo 15. Initial codes were derived from established vulnerability frameworks, while emergent codes captured local nuances through thematic saturation logic and cross-case synthesis. The findings indicate that vulnerability transformation is driven not only by biophysical shifts but also by climate resilience politics, which is operationalized here through contested resource allocation and coordination failures within local governance. While traders strive to optimize social capital and informal solidarity networks as a form of autonomous adaptation, these efforts are constrained by asymmetric power relations and a lack of integrative policy support. The study posits that sustainable resilience is impeded by a reactive-formalist paradigm in disaster management. To address this discrepancy, a transition toward collaborative governance is imperative, emphasizing the symbiotic alignment between state-led infrastructure and community-based early warning systems to navigate the increasingly unpredictable climate risks in riparian urban environments.